A COMPARATIVE STUDY OF MAYO’S REPAIR AND MESH REPAIR IN THE MANAGEMENT OF PARAUMBILICAL HERNIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Paraumbilical hernia is a common abdominal wall defect occurring through the linea alba adjacent to the umbilicus. It is more prevalent in adults and frequently associated with factors that increase intra-abdominal pressure, such as obesity, pregnancy, and chronic cough. Surgical repair is the definitive treatment, with Mayo’s repair traditionally used for many years. However, due to relatively higher recurrence rates with suture-based techniques, mesh repair has emerged as the preferred method for reinforcement of the abdominal wall. Comparative evaluation of these two techniques is important to determine the most effective approach in terms of operative outcomes, complications, and recurrence rates. Methods: This prospective cross-sectional hospital-based study was conducted in the Department of General Surgery at ACS Medical College and Hospital over a period of two years. A total of 120 patients diagnosed with paraumbilical hernia were included using simple random sampling. Patients underwent either Mayo’s repair (n=43) or mesh repair (n=77). Data were collected using a structured proforma including demographic details, BMI, smoking history, hernia type, defect size, operative details, postoperative complications, and recurrence. Statistical analysis was performed using SPSS software, with significance considered at p < 0.05. Results: Among the 120 patients studied, 64.2% underwent mesh repair and 35.8% underwent Mayo’s repair. The mean age of patients was comparable between groups. Female predominance was observed in both groups (approximately 72%). Paraumbilical hernia was the most common type. The mean duration of surgery was significantly shorter in mesh repair (77.21 ± 11.79 minutes) compared to Mayo’s repair (82.49 ± 14.31 minutes). Hospital stay was also significantly shorter in the mesh repair group (3.49 ± 0.93 days) than in the Mayo’s repair group (5.98 ± 1.68 days). Post-operative complications were lower in mesh repair (32.5%) compared to Mayo’s repair (76.7%). Recurrence was observed only in the Mayo’s repair group (9.3%), while no recurrence was reported in the mesh repair group. Conclusion: Mesh repair demonstrated superior outcomes compared to Mayo’s repair, including shorter operative time, reduced hospital stay, fewer postoperative complications, and lower recurrence rates. Therefore, mesh repair can be considered a more effective and reliable technique for the management of paraumbilical hernia.